RETRACTED: Sexually transmitted infections among migrant people and wives of migrants in far western Nepal - Bohara, Madan Singh (Journal of Kathmandu Medical College, 2014)
Retraction Notice: On 19th March 2015 the research article by Madan Singh Bohara entitled "Sexually transmitted infections among migrant people and wives of migrants in far western Nepal"; [original citation: Bohara MS. Sexually transmitted infections among migrant people and wives of migrants in far western Nepal. J Kathmandu Med Coll. 2013;2(3):139-44] was retracted from JKMC on the grounds of self-plagiarism as it was also published in American Journal of Epidemiology and Infectious Diseases vol 2 number 1 January 2014 issue. The author has been black-listed for future publication in JKMC. Journal of Kathmandu Medical College Vol. 2, No. 3, Issue 5, Jul.-Sep., 2013 Page: 139-144 DOI: http://dx.doi.org/10.3126/jkmc.v2i3.9964 Uploaded date : 3/4/2014